Social implications of green growth policies from the perspective of energy sector reform and its impact on households - Peter Heindl; Andreas Löschel (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2015)
This paper reviews the literature on distributional effects of energy and carbon taxation with focus on microsimulation models. Most studies find that direct energy and carbon taxation tends to be regressive. Regressive effects occur mostly with respect to taxation of electricity or space heating. Taxation of transportation fuels show less regressive, neutral, or even progressive effects. Adequate revenue recycling often allows for neutralisation or full elimination of regressive effects so that energy and carbon tax reforms can be progressive. Some studies find evidence for the existence of a double dividend. There seems to be an efficiency-equity trade-off in revenue recycling, i.e. whether to foster growth or to assist low-income households. While a large number of studies on advanced economies are available, there clearly is a gap with regard to evidence for developing countries. Another gap relates to the lack of documentation on the challenges of incorporating macroeconomic models and long-term modelling perspectives in microsimulation. Both aspects can be of great importance with respect to the design of green growth policies. Thoughtful incorporation of social considerations, including aspects of poverty in modelling approaches could enhance the existing instruments of exante policy assessments since poverty is a tangible concept which is well-known, understandable, and openly observable for citizens and policy makers.
Keywords: H23; H31; Q54; 330; Distributional Effects; Environmental Tax Reform; Green Growth; Energy Poverty; Microsimulation